Enhanced mechanical properties of AZ91 magnesium alloy by asynchronously large-strain high-efficiency rolling with bimodal grain structure - Dongxiao Wang; Yi Jing; Yang Gao; Jianping Li; Yuan Shi; R.D.K. Misra (Journal of Materials Research and Technology, 2023)
The study describes large strain high-speed asynchronous rolling process to process AZ91 magnesium alloy sheets with an overall thickness reduction of 84 % via two-pass rolling at 350 °C. Rolling speed ratios of 1.0, 1.1, 1.2, and 1.3 were used to obtain bimodal grain structure with different organizational states. Microstructural analysis unraveled that the formation of the bimodal structure was a consequence of combined effect of precipitation-strengthening and the Zener pinning effect. The R3 exhibiting an asynchronous ratio of 1.2 exhibited an optimized bimodal grain structure characterized by smaller recrystallized grains and a more homogeneous distribution. This phenomenon underscored the beneficial impact on enhancing strength and alleviating the anisotropic behavior.